Sufism-Based Management for Enhancing Employee Performance in Industry 4.0: A Phenomenological Inquiry - Suwito Suwito; Ischak Suryo Nugroho; Maulana Mualim; Eka Septiani Sarastuti (Teosofia: Indonesian Journal of Islamic Mysticism, 2023)
Sufism is conceptualized as a spiritual discipline oriented toward moral and spiritual refinement, and its integration into human resource management is underutilized. This article examines the concept of Sufism-based management implemented at the Faculty of Tarbiyya and Teacher Training at UIN Prof. K.H. Saifuddin Zuhri Purwokerto. The faculty applies Sufi-oriented management to cultivate inner transformation and enhance employee performance in the current business context of Industry 4.0. Using a qualitative phenomenological approach, data were collected through observation, interviews, and document analysis involving 12 key informants. The analysis guided by Smith’s model revealed that Sufi-trained business leaders demonstrate more astute organizational behavior, greater innovativeness, and stronger commitment to addressing institutional challenges. The study found that Sufism-based management elevates institutional service quality across internal, external, and transcendental dimensions, aligning organizational practices with spiritual refinement and collective well-being. Contribution: This study contributes to the literature on Sufism-based management by providing practical implementations of takhallī, taḥallī, and tajallī in business management.